Antibody Responses to Antigenic Targets of Recent Exposure Are Associated With Low-Density Parasitemia in Controlled Human Plasmodium falciparum Infections - van den Hoogen, Lotus L.; Walk, Jona; Oulton, Tate; Reuling, Isaie J.; Reiling, Linda; Beeson, James G.; Coppel, Ross L.; Singh, Susheel K.; Draper, Simon J.; Bousema, Teun; Drakeley, Chris; Sauerwein, Robert; et al. (Frontiers in Microbiology, 2019)
The majority of malaria infections in low transmission settings remain undetectable by conventional diagnostics. A powerful model to identify antibody responses that allow accurate detection of recent exposure to low-density infections is controlled human malaria infection (CHMI) studies in which healthy volunteers are infected with the Plasmodium parasite. We aimed to evaluate antibody responses in malaria-naïve volunteers exposed to a single CHMI using a custom-made protein microarray. All participants developed a blood-stage infection with peak parasite densities up to 100 parasites/µl in the majority of participants (50/54), while the remaining four participants had peak densities higher than 100 parasites/µl but lower than 200 parasites/µl. There was a strong correlation between parasite density and antibody responses associated with the most reactive blood-stage targets one month after CHMI (Etramp 5, GLURP-R2, MSP4 and MSP1-19; Spearman’s ρ=0.82, p<0.001). Most volunteers developed antibodies against a potential marker of recent exposure: Etramp 5 (37/45, 82%). Our findings justify validation in endemic populations to define a minimum set of antigens needed to detect exposure to natural low-density infections.